(untitled) (INNOVATIVE ECONOMY, 2023)
Danylenko-Kulchytska V.A. HOTEL AND RESTAURANT BUSINESS OF UKRAINE DURING THE WAR: PROSPECTS OF SURVIVAL Purpose. The aim of the article is to find out the extent of the impact of the war on the domestic hospitality industry and to propose ways to solve some of the problems caused by it. Methodology of research. General scientific and special methods were used in the research process, in particular: methods of analysis and synthesis – when justifying the process of operation of hotels and restaurants; methods of observation and logical generalization – when considering the peculiarities of the functioning of hospitality establishments in the conditions of war. Findings. It was noted that for many institutions the impact of the war was catastrophic and led to the fact that they were forced to stop their work; at the same time, any crisis leads to the emergence of new opportunities. The changes in doing business caused by the war are analyzed. It was found that today the key indicator of the efficiency of the hotel and restaurant business is the absence of losses and facilities that need subsidies. It was noted that the situation is more optimistic in the west and in the center of Ukraine. The main reason for this was the forced and sudden arrival of a large number of internally displaced persons in this region. Despite a significant decline in the first months of the war, today most of the catering establishments of the western and central regions have reached the pre-war level in terms of sales. It has been found that the main problems created by the war for hospitality enterprises are: physical destruction of establishments, disruption of logistics chains, drop in the purchasing power of the population, increase in the cost of production, outflow of qualified workers abroad. Considered possible steps that can be taken by hotel and restaurant establishments in order to maintain their positions in the market, in particular: replacing some ingredients with others, flexibly updating the menu, creating their own supply chains, organizing their own imports, strict control of income and expenses, opening new establishments in in safe regions of Ukraine or abroad, relocation of business to other regions of Ukraine, temporary refusal of marketing activities, change of payment form and work schedules, etc. It is proposed to use the positive experience of the post-war economic recovery of the hotel and restaurant sector in countries such as Croatia, Cyprus, and Georgia. Originality. It has been established that an indicator of the effectiveness of the hotel and restaurant business in the conditions of war is the absence of losses and facilities that need subsidies. In today’s conditions of total unpredictability, a combination of two principles will allow companies to survive economically: systematicity (understanding of strategic goals, control system, transparent internal processes and analytics) and flexibility (speed of making creative, non-standard decisions). Practical value. The obtained research results will contribute to the effective reconstruction and restoration of the hotel and restaurant business in the post-war period. Key words: hospitality, hotel and restaurant business, war, crisis, strategies of hotels and restaurants, recovery prospects, ways to overcome the crisis.